2016
DOI: 10.1177/1747493016641965
|View full text |Cite
|
Sign up to set email alerts
|

Histologic features of acute thrombi retrieved from stroke patients during mechanical reperfusion therapy

Abstract: Acute thrombi showed different histologic features according to the stroke etiology. The distribution of platelets and proportion of red blood cells and fibrin were major distinguishing factors between stroke subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
119
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(129 citation statements)
references
References 31 publications
7
119
0
Order By: Relevance
“…8,[11][12][13] Despite this variability, however, all stroke thrombi contained significant amounts of infiltrated leukocytes. Such heterogeneity is in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,[11][12][13] Despite this variability, however, all stroke thrombi contained significant amounts of infiltrated leukocytes. Such heterogeneity is in line with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…2 The enormous clinical, economic, and social burden of ischemic stroke is in strong contrast with the limited treatment options that are available. [6][7][8][9][10][11][12][13] Recently, neutrophil extracellular traps (NETs) have been found to be implicated in thrombosis. Endovascular treatment is unfortunately not always available, and t-PA therapy is limited by the narrow therapeutic time window (4.5 hours after stroke onset) 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on histological analysis of thrombi retrieved from 36 acute stroke patients, artheriogenic emboli with a core rich in red blood cells (56.9%±12.2%) and peripherally located platelets, and cardiogenic emboli with fibrin as the predominant component (39.5%±13.5%), may be distinguished 7. Rarely, calcified thromboemboli causing a large vessel occlusion are encountered.…”
Section: Introductionmentioning
confidence: 99%
“…A previous histologic study found that the features of the clots in patients with undetermined etiology were like those of cardiogenic thrombi. 25 Therefore, the presence of the MSC sign in patients with acute ischemic stroke with inexplicit etiology during this hospitalization indicates the importance of the search for the cardiac sources. Anticoagulation is highly effective for reduction of recurrent stroke among patients with atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%